Serological evidence of Brucella and Leptospiral .infection in cases of abortion in bovines - GUPTA, S K (The Indian Journal of Animal Reproduction, 2023)
Abortion is a common condition reported in cows and buffaloes and is known to be responsible for loss of calf, lowered milk production and a subsequent period of infertility, (Arthur, et al., 1989). Abortion is commonly caused by brucella infection, which is prevalent in 95 out 153 countries, (Thim and Wundt, 1976). Laptospirosis has long been known to occur in cattle (Amartredjo and Campbell 1975) and is a common cause of fetal death and abortion, still birth and weak calves. The pregnancy rates also were low due to infection with leptospira hardijo, (Hanson, 1980). This study was undertaken to correlate the history of abortion cases in cows and buffaloes from field with the serological evidence of brucella / leptospira agglutinins.